Air-mattress system for ballistocardiogram-based heart rate and breathing rate estimation. Issue 1 (January 2023) - Lin, Chun-Liang; Sun, Zhen-Tai; Chen, Yang-Yi
Abstract: Sleep-related problems are widespread. Numerous devices for sleep monitoring are increasingly available, including smartwatches, sleep monitoring rings, etc. These devices accumulate and analyze a substantial quantity of physiological data. In this study, we develop a smart air-mattress system that can effectively aid health measurements. The proposed system adopts an air-mattress system to detect subtle changes in pressure and thereby collect micro physiological signals, including ballistocardiography (BCG) and breathing signals. The system uses ultrasonic signals to detect the subject's turning movements. To increase the signal recognition accuracy, the BCG signal is processed effectively to reduce noise interference engendered by the body movement during sleep and is processed using regression analysis for heart rate and breathing rate estimation. Accordingly, the proposed system is unconstrained and can be used to collect micro BCG signals, breathing signals, heart rate signals, and turning movements for the long-term health-care. Abstract : Smart mattress, Air pressure, Ultrasound, BCG, Unconstrained detection, Regression analysis.